NON-INVASIVE FOREARM SUBCUTANEOUS VEIN DEPTH ESTIMATION USING MULTISPECTRAL IMAGING AND DIFFUSE REFLECTANCE IMAGES - GOH , CHUAN MENG (2018)
The estimation of subcutaneous vein depth has been an important research topic in recent years due to its importance in optimizing the intravenous (IV) access of venipuncture. Various techniques and system of vein visualization were proposed to improve the vein viewing, but the lack of vein depth information limits the system performance in assisting the IV access; thus, the IV access in many cases remains dependent on skill or experience of the clinicians.